Rancang Bangun Antena Mikrostrip MIMO 4 Elemen Untuk Komunikasi 5G Pada Frekuensi Band N40 - Fannush Shofi Akbar; Aulia Saharani (Emitor: Jurnal Teknik Elektro, 2022)
This study discusses the design of the MIMO microstrip antenna which is implemented in a 5G communication system that works on the N40 frequency band (2.3-2.4 GHz) with the center frequency of 2.35 GHz. The parameters that are unique of this antenna is focusing on the mutual coupling and correlation of MIMO antennas. The MIMO configuration was chosen because it can meet the high data transmission needs of 5G communication systems. The antenna is composed of a square patch with a microstrip insert feed-line technique. Then, the substrate uses FR-4 material, with a dielectric constant value of 4.3. After the design of a single element antenna that works according to the criteria is obtained, then the antenna is arranged into a configuration of 4 parallel elements, a 2×2 MIMO configuration with uniform polarization, and a 2×2 MIMO configuration with non-uniform polarization. After the design process, the antenna design is fabricated and then measured using a Vector Network Analyzer (VNA). The analysed antenna parameters are return loss, mutual coupling, Voltage Standing Wave Ratio (VSWR), bandwidth, and radiation pattern. From the element measurement results, it is found that the return loss is -11.24 dB and the bandwidth is 70 MHz at the center frequency of 2.35 GHz. As for the analysis of mutual coupling between elements, the best results were obtained from the MIMO configuration of 2×2 non-uniform polarization with values -20 dB for all elements. The antenna measurement results obtained indicate a similarity with the simulation results. This result is suitable for MIMO applications that require very low mutual coupling and correlation between elements.